Corneal topography : from theory to practice - Kiliç, Aylin; Roberts, Cynthia J. (Kugler Publications, 2013)
PrefaceKiliç and Roberts have assembled a strong team of experts to create a treatise of extraordinary value to the eye care professionals. Modern corneal topography is presented from the fundamental concepts, to the descriptions of representative instruments available, to a selection of the many applications to which this technology has applied itself. The field began as a quest to show the pioneers of keratorefractive surgery how the corneal surface was surgically altered. This provided guidance for the remarkable achievements that followed.